The gas proportional scintillation counter/microstrip gas chamber hybrid detector - Freitas, D. S. A. P. (2003)
The gas proportional scintillation counter/microstrip gas chamber (GPSC/MSGC) hybrid detector for X-ray spectrometry is described. The detector uses a CsI-coated microstrip plate placed in direct contact with the gas-filling as the photosensor readout for the GPSC scintillation substituting for the photomultiplier tube (PMT). Usable photosensor maximum gain is limited by optical positive feedback due to the additional scintillation produced in the electron avalanche process at the MSP anodes, in the absence of quenching. A low-photoelectron collection efficiency is achieved in the gas atmosphere, resulting in a scintillation conversion efficiency that is about a factor of 5 lower than that achieved with PMT-based GPSCs. However, energy resolutions of 11% for 5.9 keV X-rays are achieved with this detector.